Neither here nor there : the many voices of liminality - Carson, Timothy L.; Taylor, Barbara Brown (The Lutterworth Press, 2019)
An interdisciplinary anthology of essays exploring the concept of liminality and its fruitful application across a wide range of contemporary subjects.